Metabolic atrophy and 3‐T 1H‐magnetic resonance spectroscopy correlation after radiation therapy for prostate cancer. (20th February 2014) - Panebianco, Valeria; Barchetti, Flavio; Musio, Daniela; Forte, Valerio; Pace, Alberto; De Felice, Francesca; Barchetti, Giovanni; Tombolini, Vincenzo; Catalano, Carlo
<x xml:space="preserve">Abstract</x> Objective To correlate 3‐T magnetic resonance spectroscopic imaging (MRSI) with prostate‐specific antigen (PSA) levels in patients with prostate cancer treated with external beam radiation therapy to assess the potential advantages of MRSI. Materials and Methods A total of 50 patients (age range 65–83 years) underwent PSA and MRSI surveillance before and at 3, 6, 12, 18 and 24 months after radiotherapy. Results Of the 50 patients examined, 13 patients completely responded to therapy showing metabolic atrophy (MA), defined as a choline‐plus‐creatine/citrate (CC/C) ratio <0.2, at 3 months; in this group none had biochemical relapse (PSA nadir + 2 ng/mL) by the end of the follow‐up. Of the 50 patients, 35 showed a partial response to therapy (CC/C ratio between 0.2 and 0.8) at 3 and 6 months and, of these 35 patients, 30 reached MA at 12 months, while five developed a recurrence (CC/C ratio >0.8). Three of those patients with recurrence had a biochemical relapse at 18 months and the other two at 24 months. Two of the 50 patients did not respond to the treatment, showing persistent disease from the 3rd month (CC/C ratio >0.8); one patient had biochemical relapse at 6 and the other at 12 months. Conclusions MRSI was shown to have a greater potential than PSA level in monitoring patients after radiotherapy, because it anticipates PSA nadir, and biochemical relapse in particular.